Numerical direct Laplace transform - Tuluchenko, Halyna Yakivna; Berezhnoi, Vladyslav Danylovych (Харківський національний університет імені В. Н. Каразіна, 2024)
A Maplet-application has been developed for performing approximate direct Laplace transform using composite quadrature formulas that use orthogonal polynomials expansions. The application has a modular structure, which allows to supplement the library of used quadrature formulas. It is intended to use the application in the educational process and to conduct computational experiments in scientific research.
Keywords: composite quadrature formulas; orthogonal polynomials; composite quadrature formulas